THE RATIONALITY OF ANTIBIOTIC USE ON PATIENTS OF TYPHOID FEVER - Hudi, Riefki Indira; Ranti, Imaniar (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2020)
Typhoid fever is an infectious disease caused by Salmonella typhi bacteria. The administration of antibiotics in typhoid fever is needed as a causative therapy to eradicate the bacteria based on the principles of rational therapy to avoid antibiotic resistance. However, there are still a considerable amount of cases of unnecessary antibiotic administration. This study aims to examine the rationality of antibiotic use on patients of typhoid fever. This research is a non-intervention study with descriptive analytic methods. Data were retrieved retrospectively by identifying the medical records of patients treated in the X Hospital Salatiga from January to August 2016 with a purposive sampling method based on the inclusion and exclusion criteria of 67 cases. The data was analyzed by using Gyssen criteria based on the standard of typhoid fever service of WHO 2011. The result showed that the percentage of female typhoid fever patients was higher than the male with the most prolonged 3-day hospitality. The most commonly used antibiotics are ceftriaxone, ciprofloxacin, and cefixime with the result of the rationality analysis of category 0 (55.22 %), category IIIA (1.49%), category IIIB ( 8.96% ), category IVA (17.91%), and category IVC (4.48%). It can be concluded that  the rationality of antibiotics used in patients with typhoid fever at X Hospital Salatiga based on Gyssen criteria showed a good result.